2023
DOI: 10.1101/2023.01.12.523844
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Functional gene delivery to and across brain vasculature of systemic AAVs with endothelial-specific tropism in rodents and broad tropism in primates

Abstract: Delivering genes to and across the brain vasculature efficiently and specifically across species remains a critical challenge for addressing neurological diseases. We have evolved adeno-associated virus (AAV9) capsids into vectors that transduce brain endothelial cells specifically and efficiently following systemic administration in wild-type mice with diverse genetic backgrounds and rats. These AAVs also exhibit superior transduction of the CNS across non-human primates (marmosets and rhesus macaques), and e… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 78 publications
1
16
0
Order By: Relevance
“…Our results validate the utility of cell microarray screening to identify receptors for natural and engineered AAVs. We identify LRP6 as a novel and highly conserved target for blood-brain barrier transcytosis by AAV9-X1.1, a potent engineered capsid for primate neurons 20 and human IL3 as an interaction partner for AAV9. These findings offer the prospect of leveraging identified receptors for targeted drug delivery across diverse therapeutic modalities, such as small molecules, antibodies, or oligonucleotides.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results validate the utility of cell microarray screening to identify receptors for natural and engineered AAVs. We identify LRP6 as a novel and highly conserved target for blood-brain barrier transcytosis by AAV9-X1.1, a potent engineered capsid for primate neurons 20 and human IL3 as an interaction partner for AAV9. These findings offer the prospect of leveraging identified receptors for targeted drug delivery across diverse therapeutic modalities, such as small molecules, antibodies, or oligonucleotides.…”
Section: Discussionmentioning
confidence: 99%
“…AAV capsid engineering, particularly through directed evolution methods, has demonstrated that markedly improved efficiency in desired cell types and tissues after systemic intravenous delivery is possible 1719 . In particular, two recently identified engineered capsids, AAV9-X1.1 20 and AAV.CAP-Mac 21 , robustly transduce CNS neurons after systemic administration in macaque. As AAV capsids are applied across species however, the enhanced tropisms of many engineered vectors can vary 22,23,20,21 .…”
Section: Introductionmentioning
confidence: 99%
“…Despite having significant potential for research on lesser-studied species not amenable to transgenesis, broader use of AAVs has been limited. These viral vectors have only recently been employed in neuroscience applications in non-human primates 103,104 , birds [105][106][107][108] , and reptiles 109 . Previous experiments in zebrafish 110 and frogs 42 either did not find, or found negligible, AAV transduction in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Diversification of the AAV capsid through directed evolution has yielded a toolkit of AAVs with varied tissue tropism [11][12][13][14][15][16][17][18][19][20][21][22][23] . Further refinement of expression can be achieved through inclusion of regulatory elements, including enhancer sequences [24][25][26][27][28][29][30][31][32][33] .…”
Section: Discussionmentioning
confidence: 99%
“…Maintenance of the AAV genome as circular monomeric or concatemeric episomes provides long-term expression [6][7][8][9][10] . The tropism of AAVs can be altered by modifying residues on the AAV capsid surface and directed evolution has yielded a toolkit of capsids with diverse tropisms, including variants that can efficiently and broadly transduce target organs following systemic administration [11][12][13][14][15][16][17][18][19][20][21][22][23] .…”
Section: Introductionmentioning
confidence: 99%